Comparison of Cardiovascular Medicines Prices in Four European Countries - Mitkova, Zornitsa; Vasileva, Mariya; Savova, Alexandra; Manova, Manoela; Terezova, Silvia; Petrova, Guenka (Frontiers in Public Health, 2020)
The aim of the current study was to compare pricing methodologies at the manufacturer, wholesale, and retail levels, and to estimate the price differences of AT1-receptor blockers (sartans), Angiotensin-converting enzyme (ACE)—inhibitors, and their fixed-dose combinations (FDCs) in four countries using similar methodologies: Slovakia, Greece, Bulgaria, and Romania (SK, GR, BG, and RO, respectively). The methodologies for manufacturer, wholesale, and retail price establishment have been compared using nationally implemented rules. Overlapping trademarks were established retrospectively on the manufacturer and retail levels in November 2017. The average price per tablet, percentage of price deviation, and statistically significant differences were calculated. The selected countries apply external reference pricing at the manufacturer level. A wide variation in the number of referent countries was observed (from 12 to 27). Despite the use of a regressive scale for price calculation, large variations between margins and value-added tax (VAT) are established, thus leading to different final medicine prices. This study found that medicine prices were lower in RO than in other selected countries. It was caused by the fact that 15 products had the lowest manufacturer price and 14 products had the lowest retail price in RO. Results of Kruskal–Wallis test showed that there were no significant differences between prices per tablet on the manufacturer and retail levels. In the group of fixed-dose combinations, ramipril/hydrochlorothiazide, and irbesartan/hydrochlorothiazide showed more than 100% deviation. The prices of cardiovascular medicines differed within the observed countries. The differences in pricing methodologies (e.g., margins, VAT) at the national level did not significantly affect retail prices, as a low manufacturer price usually leads to a low retail price.